The school knowledge in biodiversity in terms of re-signifying its teaching - De La Cruz, Lizeth Paola; Pérez, Nabi Del Socorro (Universidad Pedagógica y Tecnológica de Colombia, 2020)
A synthesis of the results of a formative assessment conducted with students of junior hihg school is presented. The objective was to investigate their conceptions about biodiversity in order to reveal the formative needs that require strengthening in the teaching of this field of knowledge. A qualitative methodology was used and, from the hermeneutic paradigm, techniques such as semi-structured interviews, analysis of graphic organizers and observation guide were employed. The results prove that most students have basic competence in the contents related to biodiversity, restricted to the animal andvegetal organisms. This reflects a low level in establishing connections, since concepts such as genetic and ecosystemic diversity, adaptation, evolution, among others, are dismissed. Thus, it is necessary to strengthen in the students the complex relational knowledge through didactic strategies to resignify the teachinglearning process.